The role of organic amendments in wetland restorations. Issue 4 (2nd June 2020) - Scott, Brian; Baldwin, Andrew H.; Ballantine, Kate; Palmer, Margaret; Yarwood, Stephanie
Abstract : At the present rate of loss (since 1990), half of the remaining wetlands worldwide will be developed within ~140 years, underscoring the importance of improving the creation and restoration of wetlands. Organic amendments are sometimes used during wetland creation. To evaluate the effectiveness of adding organic amendments we used a combined numerical method to assign "scores" on five categories of evaluation metrics: plant growth, soil properties, carbon accrual, denitrification, and anaerobic processes (e.g. redox potential). We found that amendments identified as "topsoil" scored measurably higher and had consistently more positive values with fewer negative results compared to amendments identified as "allochthonous organic matter" (alOM). Organic amendments had about the same effect on soils with low soil organic carbon (<2.5%) compared to soils richer in organic carbon. Organic amendments are not uniformly effective, and in some cases may have negative side effects. For example, alOM often resulted in a loss of plant diversity. These outcomes along with site conditions should be evaluated before using organic amendments.